Hyperactivation of proprioceptors induces microglia-mediated long-lasting pain in a rat model of chronic fatigue syndrome - Masaya Yasui; Yuki Menjyo; Kyohei Tokizane; Akiko Shiozawa; Makoto Tsuda; Kazuhide Inoue; Hiroshi Kiyama (Journal of Neuroinflammation, 2019)
Abstract Background Patients diagnosed with chronic fatigue syndrome (CFS) or fibromyalgia experience chronic pain. Concomitantly, the rat model of CFS exhibits microglial activation in the lumbar spinal cord and pain behavior without peripheral tissue damage and/or inflammation. The present study addressed the mechanism underlying the association between pain and chronic stress using this rat model. Methods Chronic or continuous stress-loading (CS) model rats, housed in a cage with a thin level of water (1.5 cm in depth), were used. The von Frey test and pressure pain test were employed to measure pain behavior. The neuronal and microglial activations were immunohistochemically demonstrated with antibodies against ATF3 and Iba1. Electromyography was used to evaluate muscle activity. Results The expression of ATF3, a marker of neuronal hyperactivity or injury, was first observed in the lumbar dorsal root ganglion (DRG) neurons 2 days after CS initiation. More than 50% of ATF3-positive neurons simultaneously expressed the proprioceptor markers TrkC or VGluT1, whereas the co-expression rates for TrkA, TrkB, IB4, and CGRP were lower than 20%. Retrograde labeling using fluorogold showed that ATF3-positive proprioceptive DRG neurons mainly projected to the soleus. Substantial microglial accumulation was observed in the medial part of the dorsal horn on the fifth CS day. Microglial accumulation was observed around a subset of motor neurons in the dorsal part of the ventral horn on the sixth CS day. The motor neurons surrounded by microglia were ATF3-positive and mainly projected to the soleus. Electromyographic activity in the soleus was two to three times higher in the CS group than in the control group. These results suggest that chronic proprioceptor activation induces the sequential activation of neurons along the spinal reflex arc, and the neuronal activation further activates microglia along the arc. Proprioceptor suppression by ankle joint immobilization significantly suppressed the accumulation of microglia in the spinal cord, as well as the pain behavior. Conclusion Our results indicate that proprioceptor-induced microglial activation may be a key player in the initiation and maintenance of abnormal pain in patients with CFS.